Vibrational Impact on Milled Surface Irregularities - Lishchenko N. V.; Larshin V. P.; Pitel J. (Журнал інженерних наук)
The methodology and results of a simultaneous study of causally linked parameters of mechanical vibration (cause) and surface irregularities (consequence) in flat milling with an end mill are given. The features of measurement and analysis of surface quality parameters through the application of the separation frequency method of profilogram harmonic components on the surface roughness, waviness, and the deviation of the profile are reviewed. A new method of profilogram digital processing is developed, comprising the steps of its digitization, low-pass filtering, and the formation of the roughness profile. The initial theoretical positions on modeling mechanical (elastic) waves which are caused by vibration in the cutting zone and propagate in a solid, liquid, and gas (air) media are presented. The results of experimental studies of milled surface profilogram and the vibro-displacement signal in the milling are given.